Diskursus Humor dan Etika dalam Perspektif Al-Qur'an - Muhamad Yoga Firdaus; Wahyudin Darmalaksana (MAGHZA, 2021)
This study aims to discuss the ethics of humor from the perspective of the Al-Qur'an. This research method is qualitative through literature study with a social psychology approach. The results and discussion of this research include the discourse of humor and ethics and the ethics of humor from the perspective of the Al-Qur'an through social psychological analysis. This study concludes that the Al-Qur'an provides moral messages about the ethics of humor through motivation and positive emotions to produce good interactions and become guidelines for happiness in social life. This study recommends fostering a culture and humorous behavior by strengthening the ethical base of moral messages from religious texts, especially for Muslims.